I Want Music to Express What Is Going on in South America. the Third-World Music Turn in Leandro “Gato” Barbieri’s Jazz Style (Revista Argentina de Musicología, 2020)
Today, when contemporary jazz musicians are willing to beyond the canonic tradition of jazz, the music of composer and saxophonist Leandro “Gato” Barbieri acquires a pioneering and groundbreaking significance. With his music, a new musical conversation started between jazz and Latin American folk genres (mainly from Argentina and other regions of South America). Barbieri had been a widely acclaimed musician for a long time in the European free jazz style scene by the time he took a decisive musical turn that would drive his music closer to the cultural and political milieu of his time. His political choices coincided with the onset of civil right movements and a new revolutionary spirit that was rising in Latin America during 1969-1975. As the working title of this paper suggests, I will examine the ways and cultural significance of what could be called the “Third World Music Turn” in the music of Argentina’s most famous jazz musician.
Keywords: Barbieri; Jazz; Revolution; Latin America; Music; 60s/70s